Understanding the visual - Schirato, Tony; Webb, Jen (Sage, 2004)
In a world preoccupied with the visual, it has become essential to understand the dynamics of images and interpret them. This volume shows the reader how to analyse the structure, conventions, contexts and uses of the visual in Western cultures.